2020
DOI: 10.1113/ep088096
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in mitochondrial functions and morphology in muscle and non‐muscle tissues in type 1 diabetes: implications for metabolic health

Abstract: We recently made the observation that there are significant alterations to the ultrastructure and functions of mitochondria in skeletal muscle of people with type 1 diabetes (T1D). These alterations are proposed to lead to decreased energy production in skeletal muscle during exercise and thus may contribute to the impaired aerobic exercise capacity reported in some people with T1D. This Symposium Review summarizes the evidence that similar alterations also occur in the mitochondria present in organ systems ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Participants were randomly assigned to complete one of three video-guided exercises (aerobic, interval, or resistance) at home for a total of at least six sessions throughout a 4-week observational period. Study exercise assignment was stratified by insulin administration method (HCL, standard pump, or MDI), age group (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), or 45-70 years), and sex. Study videos were 30 min in duration, including warm-up and cool-down periods that lasted $3 min each, and were designed to elicit a target heart rate based on exercise type: 70-80% of the agepredicted maximal heart rate (aerobic), up to 80-90% of age-predicted maximal (interval), or major muscle group fatigue after three sets of eight resistance-band repetitions (resistance).…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Participants were randomly assigned to complete one of three video-guided exercises (aerobic, interval, or resistance) at home for a total of at least six sessions throughout a 4-week observational period. Study exercise assignment was stratified by insulin administration method (HCL, standard pump, or MDI), age group (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), or 45-70 years), and sex. Study videos were 30 min in duration, including warm-up and cool-down periods that lasted $3 min each, and were designed to elicit a target heart rate based on exercise type: 70-80% of the agepredicted maximal heart rate (aerobic), up to 80-90% of age-predicted maximal (interval), or major muscle group fatigue after three sets of eight resistance-band repetitions (resistance).…”
Section: Study Design and Populationmentioning
confidence: 99%
“…The ability to oxidize lipids and carbohydrates during incremental exercise reflects a profile of metabolic fitness correlated to the physiological status of the muscles (Brun et al, 2012;Zakrzewski and Tolfrey, 2012). There could, therefore, be an impaired muscle function during exercise, especially since it has been demonstrated that in young adults with T1DM, skeletal muscle mitochondria have irregularly organized cristae at the ultrastructural level, a decreased ability to produce adenosine triphosphate in response to increasing energy demand, and an increase in complex III-derived reactive oxygen species subsequent to fatty acid oxidation (Monaco et al, 2020). Furthermore, research has found reductions in skeletal muscle mitochondrial oxidative phosphorylation in adolescents with T1DM, which may be linked to insulin resistance, potentially through altered redox signaling (Fisher-Wellman and Neufer, 2012;Monaco et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Participants were randomly assigned to complete one of three video-guided exercises (aerobic, interval, or resistance) at home for a total of at least six sessions throughout a 4-week observational period. Study exercise assignment was stratified by insulin administration method (HCL, standard pump, or MDI), age group (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), or 45-70 years), and sex. Study videos were 30 min in duration, including warm-up and cool-down periods that lasted $3 min each, and were designed to elicit a target heart rate based on exercise type: 70-80% of the agepredicted maximal heart rate (aerobic), up to 80-90% of age-predicted maximal (interval), or major muscle group fatigue after three sets of eight resistance-band repetitions (resistance).…”
Section: Study Design and Populationmentioning
confidence: 99%